If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10c + -4c + 2 = 20 Reorder the terms: 2 + 10c + -4c = 20 Combine like terms: 10c + -4c = 6c 2 + 6c = 20 Solving 2 + 6c = 20 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6c = 20 + -2 Combine like terms: 2 + -2 = 0 0 + 6c = 20 + -2 6c = 20 + -2 Combine like terms: 20 + -2 = 18 6c = 18 Divide each side by '6'. c = 3 Simplifying c = 3
| (-2r)+(17r)+(-2r)=13 | | (-18u)+(12u)+(2u)-(1)=15 | | 10=(.75)F+7 | | -18u+12u+2u-1=15 | | 4x-3=9x+2 | | 8x+4-10=5 | | 8x+4-10=-5 | | n-3-5n^2-n+5= | | x-3u-18=0 | | x^3-49x^2-52x+100=0 | | 6x-1+5=7 | | (18a)+(-20a)=-8 | | y^4+y^2-20=0 | | 6x-1+5=-7 | | 7(7x-3)=49x-21 | | 2x+4-9=-2 | | 9(y+8)+y=3(y+5)+6 | | 3x-8=4(x-2) | | 3x-y+9=0 | | -7(n+4)=-6n-2 | | 3(2-4(1+x))=5-3(3-x) | | -4=z+6 | | 2-w=3+w | | (-9v)-(-11v)-(20v)-(-12v)=18 | | -294x-5=2x | | ((2x^2)y)(-3x^3y^2)= | | 6(t-2)+6t=6(2t+2)-8 | | 15k+4k-16k-k-k=11 | | 8q-9(q-8)+8(p-8)= | | 13h-5h-h=7 | | -3(3s-4)-12=-2(7s+0)-3 | | 15h-5h-h=7 |